The aesthetic-pedagogical thought of Joseph Beuys: between memory and performance - Cercós i Raichs, Raquel (Historia y Memoria de la Educación, 2016)
The figure of the German artist Joseph Beuys (1921-1986) stands out not only for their artistic creations but for having created a complex and suggestive aesthetic-pedagogical discourse whose outline we offer here. The focus of attention will be tow and for its temporal specificity the will be presented as follows: the first start from the ruins of World War II to address issues relating to the crisis of language and the subject and to highlight the efforts of the artist to set up a theoretical and practical discourse on the aesthetics of memory, a process of anamnesis able to dismantle the institutionalized silence about Nazism. The second traces the sixties to the eighties, when Beuys adopted the performance as a means of expression and exegesis. A concept and practice that will be joined by others as Formung (plastic deformation), social plastic or social sculpture that ultimately allow us to outline what education means in postmodern times.